Faktor-Faktor Yang Mempengaruhi Pendapatan Transmigran Di Kabupaten Tabalong (Studi Kasus Transmigran Di Kelurahan Argomulyo) - Andrey, Andrey Irawan; Rahmini, Noor (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The problems that occur among transmigrants, namely poverty is often associated with low income or low income, therefore low income can affect the transmigration program. To measure the income of transmigrant communities, you can look for variables related to income such as level of education, capital. effort, costs, work period, and work hours. This research aims to find out what factors can influence the income of transmigrants in Argomulyo village. The analysis used in this research is multiple linear regression analysis. The data sources are primary and secondary data. The results of the research are that capital, length of service, working hours and level of education simultaneously influence the income of transmigrants in Argomulyo Village. The dominant independent variable that partially influences transmigrants' income is working hours, and the independent variable that does not partially influence income is capital.